Model Matematika Terapi Hormon pada Kanker Payudara Menggunakan Jaringan Kanker Linear - rizqa hariq hazana; muhammad subhan (UNIVERSITAS NEGERI PADANG, 2019)
Abstract—Cancer is a disease in which abnormal growth of cells occurs. Breast cancer is a cancer that starts in the breast vessels which is usually known as epithelias cells. The goal of this study is to form a mathematical model that can illustrate how hormone therapy prevents estrogen receptors in breast epithelial cells to help cancer cells divide. Model is a differential equation system which has four equations and five fixed points. From the results of the analysis it was found that the fixed point P1 is always unstable, while the fixed points P2 to P5 are stable depending on certain conditions.Keywords—Mathematical Models, Breast Cancer, Hormone Therapy, Linear Cancer Network.